Public relations writing : - Bivins, Thomas H. (McGraw-Hill, 2005)
This text equips students with the essential skills for developing and writing public relations materials, covering all areas of public relations writing--including news releases, backgrounders, newsletter and magazine articles, brochures, print advertising copy, and broadcast scripts. Recent technological changes are also covered to give students an understanding of how technology impacts the public relations industry. In the constantly changing world of public relations, the text continues to stress the need for public relations professionals to communicate more effectively to all audiences